Hattischer Wortschatz in hethitischer Textüberlieferung - Soysal, Oğuz. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2004)
The particular aim of this volume is an extensive compilation of Hattian words based on Hittite written sources. It sets itself the task of listing all Hattian lexical elements alphabetically as they occur as words or in word combinations, with text references, and relevant bibliography. The main part of the book, the \'List of Hattian Words,\' contains morphological analyses of the Hattian lexemes, their Hittite equivalents in the bilingual documents as well as the lexical elements Hittite borrowed from Hattian. Apart from the word list this study offers information on the Hattian text corpus, Hattian phonetics, grammar and semantics.